2003
DOI: 10.1002/elps.200305382
|View full text |Cite
|
Sign up to set email alerts
|

Peak dispersion and contributions to plate height in nonaqueous capillary electrophoresis at high electric field strengths: Propanol as background electrolyte solvent

Abstract: Peak dispersion effects in nonaqueous capillary electrophoretic separations of aromatic anionic analytes were investigated in a propanolic background electrolyte solution. Poly(glycidylmethacrylate-co-N-vinylpyrrolidone) coating was applied to the capillary to suppress the electroosmotic flow and to improve the repeatability of the migration times. Electrical field strengths up to 2000 Vcm(-1) were applied in separations and the separation efficiencies were compared with theoretical values calculated on the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
(24 reference statements)
1
24
0
Order By: Relevance
“…The variation will be compensated at least in part by the simultaneous variation of the velocity v, which includes the analyte mobility (see the discussion about the ratio m/D given above). The change of the rate constant of desorption, k d , upon substitution of one solvent by another is hard to predict (cf., e.g., [7,8] [34]). In general, the electrostatic interaction is thus enhanced in comparison to aqueous solutions, and the distribution constant is therefore increased.…”
Section: Peak-broadening Due To Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation will be compensated at least in part by the simultaneous variation of the velocity v, which includes the analyte mobility (see the discussion about the ratio m/D given above). The change of the rate constant of desorption, k d , upon substitution of one solvent by another is hard to predict (cf., e.g., [7,8] [34]). In general, the electrostatic interaction is thus enhanced in comparison to aqueous solutions, and the distribution constant is therefore increased.…”
Section: Peak-broadening Due To Adsorptionmentioning
confidence: 99%
“…Obviously, such data can be beneficial when planning the experimental setup, and is also valuable for the interpretation of the results obtained. In addition to MeOH and ACN other solvents, like ethanol (EtOH) [7], 1-propanol [8], propylene carbonate [9], N,N-dimethylformamide (DMF) [10], formamide (FA) [11], N,N-dimethylacetamide (DMA) [12], and nitromethane (NM) [13], have been applied to CE.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant thermal plate height has been examined both theoretically and experimentally [19][20][21][22][23][24][25]. It was found that this thermal plate height is ordinarily small compared to that caused by molecular diffusion except at some extreme conditions [24,25].…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, these authors observed concave-convex-concave fluid velocity profiles from the inlet to the outlet of the capillary [28]. Porras et al [14,15] and Palonen et al [24,25] studied the influence of solvent on the fluid temperature and the thermal peakbroadening in CZE at high electric fields. They obtained significantly low separation efficiency at high electric fields, which could not be explained by the radial temperature gradients induced thermal plate height.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation